Multidetector computed tomography for detecting left atrial/left atrial appendage thrombus: a meta‐analysis. Issue 10 (October 2015) - Zou, H.; Zhang, Y.; Tong, J.; Liu, Z.
Abstract Background The diagnostic accuracy of multidetector computed tomography (MDCT) in the detection of left atrial/left atrial appendage (LA/LAA) thrombus had been tested in many studies; however, the results are controversial. Aim The aim of the present study was to evaluate synthetically the diagnostic accuracy of MDCT in LA/LAA thrombus. Methods PubMed and Embase were searched for published prospective studies which compared computed tomography with transoesophageal echocardiography (TEE) in detecting LA/LAA thrombus prior to March 2014. Descriptive and quantitative information was extracted and MetaDiSc 1.4 was used to perform a meta‐analysis. Results Fifteen prospective clinical controlled trials with 2540 patients fulfilled the inclusion criteria. The pooled sensitivities (SEN): 0.957; pooled specificities (SPE): 0.917; pooled positive likelihood ratio (PLR): 22.017; pooled negative likelihood ratio (NLR): 0.060; pooled diagnostic odds ratio (DOR): 437.43; the area under the curve (AUC): 0.9883; Q*‐value: 0.9544. However, in the abovementioned indexes, the heterogeneities were statistically significant between studies (P < 0.05, inconsistency index (I2) > 50%). In a sub‐analysis of studies in which delayed imaging, electrocardiogram (ECG) gating and heart rate control were performed, not only the diagnostic accuracy, but also the heterogeneities were significantly improved (pooled SEN 0.991; pooled SPE 0.989; pooled PLR 60.768; pooled NLR 0.034; pooled DOR 2561.7; AUC 0.9972; Q*‐value 0.9806; all the indexes' P‐value were greater than 0.05 and the I2 were 0%, except for SPE, I2 = 54.6%). Conclusion For patients with TEE intolerance or contraindications, MDCT may be an alternative method, especially when the delayed imaging, ECG gating and heart rate control were performed.